EXPLORING THE CURRENT FLORISTIC DIVERSITY AT KOLANKI HILLS ASHAPUR RAICHUR KARNATAKA INDIA - Theophilus Deenadayal; Dr Tarun Jain (The Bioscan, 2024)
The Kolanki hills in Ashapur of Raichur District of Karnataka represent a potential hotspot for an array of highly biodiverse plants. The present research systematically records 405 plant species from 76 families indicating the area’s significance for this ecosystem. In this study, species density, abundance and frequency were determined using the quadrat method for inferring community structure. Key diversity indices, including the Shannon-Weiner Index (4.23), Simpson’s Diversity Index (1.00) and Species Richness Index (0.70), underscore the hills’ biodiversity richness and evenness. Dominant genera, such as Indigofera (10 species) and Cyperus (9 species), highlight the area’s floristic composition. The findings emphasize the need for conservation strategies to protect the ecological integrity of this semi-arid ecosystem. Insights from this study provide a foundation for sustainable management and contribute to understanding regional biodiversity.